Lost in Translation. The Gospel in Transition in Christian Beginnings - LOADER, William R. G. (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
Jesus Christ was not the son of Mr and Mrs Christ. A child or maybe an unsuspecting adult might be forgiven for thinking this was so, given that Christ does sound like Jesus’ surname. The title, Mashiach, Messiah, translated Christ, did indeed become the equivalent of a name, its original meaning lost in translation or at least in the transition as the Jesus movement moved from its Jewish culture into the cultures of the wider world. More was at stake, however, than the shift from a title to a name. Changes which the transition entailed included a shift from corporate hopes based on restoring Israel’s kingdom to universal concerns with individual salvation and the hope of heaven, from good news for the poor addressed to Israel to care for the poor primarily among believers, and from Jesus the Jewish Messiah to Jesus the Logos incarnate, and in the process the issue of continuity and discontinuity with faith’s heritage, not least in the light of what became exclusive claims to salvation.